Analysis of anatomical characteristics of congenital pulmonary airway malformation lesions based on CT images - Peng, Yongxuan; Xu, Yuejuan; Tang, Jiazhong; Qian, Ziling; Hu, Jie; Liu, Wei; Xia, Yulian; Sun, Xin; Sun, Kun; Bai, Kai; Lu, Yanan (Frontiers in Pediatrics, 2025)
ObjectiveThe surgical treatment of congenital pulmonary airway malformations (CPAM) remains a subject of debate. This study aimed to deeply analyze the preoperative CT imaging data to explore the anatomical characteristics of CPAM lesions, providing additional information to guide surgical treatment for such conditions.MethodsA retrospective analysis was conducted on the medical records of children with congenital pulmonary airway malformations who underwent surgery between 2020 and 2024 at our hospital. Preoperative CT images were processed using 3D Slicer software to analyze the volume, external boundaries, vascular and airway branching, and resection planes (lung venous branch planes) of the lesions. The primary analysis indicators included lesion volume, the volume ratio of the lesion to the affected lung lobe, and the real airway, artery, and venous branches supplying the lesion, as well as the airway, artery, and venous branches that might be severed during resection.ResultsA total of 17 cases and 18 corresponding preoperative CT images were included, with 7 cases using enhanced CT scans. The mean age of the patients was 68.9 ± 38.9 months. Most lesions (72.2%) were located in the lower lung. The average volume of the lesions was 47.5 cm3 (range: 25.6–91.4 cm3), which occupied 26.6 ± 12.7% of the affected lung lobe. There was no significant correlation between lesion volume and age (r = 0.25), and a weak negative correlation between the volume ratio and age (r = −0.48). The proportion of lesions with real supplying airway, artery, and venous branches was 16.7%, 77.8%, and 83.3%, respectively. The proportions of lesions requiring the severance of additional airway, artery, and venous branches during resection were 27.8%, 16.7%, and 5.5%, respectively. The external boundaries of the lesions were most clearly exposed.ConclusionThe use of preoperative CT imaging and corresponding image processing software allows for a comprehensive analysis of the anatomical characteristics of congenital pulmonary airway malformation lesions. This may help improve the understanding of CPAM and the effectiveness of lesion resection surgeries.